Shrimp Intestinal Microbiota Homeostasis: Dynamic Interplay Between the Microbiota and Host Immunity - Kai‐Min Zhou; Ping‐Ping Liu; Jia‐Yun Yao; Gerardo R. Vasta; Jin‐Xing Wang; Xian‐Wei Wang (Reviews in Aquaculture, 2025)
The shrimp intestine harbors a microbiota that has pivotal roles for host's physiology. Imbalance of shrimp intestinal microbiota has been shown closely related to the occurrence of diseases. The morphological and biological features of the shrimp intestine are considered suboptimal for stable microbial colonization, making the intestinal microbiota composition highly susceptible to the impact of environmental changes or stressors, and particularly unstable. Therefore, the relative unsteadiness of the microbiota composition represents a continuous threat to host survival. Shrimp intestinal microbiota homeostasis is achieved through a dynamic interplay between the microbiota and the host's innate immunity. The shrimp intestine possesses effective innate immune mechanisms that can suppress the uncontrolled proliferation of microbiota components, and simultaneously protect the microbiota from elimination. The mechanism(s) by which the microbial components and the intestinal innate immunity interact with each other to achieve homeostasis represents an interesting interplay between host and microbiota. This review summarizes the current knowledge about intestinal microbiota colonization in shrimp, as well as the intricate mechanisms employed by the intestinal immune system to regulate this microbiota. Moreover, the potential intervention strategies to promote and protect shrimp intestinal homeostasis by modulating the microbiota are also discussed. Thus, this review seeks to comprehensively analyze the current information and contribute to a deeper understanding of the complex interplay between the shrimp intestinal microbiota and innate immunity in maintaining shrimp intestinal homeostasis and overall health. This enhanced understanding may potentially open new avenues for aquaculture management and disease mitigation strategies, ultimately benefiting the shrimp farming industry.